(untitled) (Bangladesh Journal of Botany, 2019)
Small balls of ‘Ladoos’ were made by using blended aonla fruit of three cultivars with refined and raw sugar, ginger and cardamom flavours. The prepared ‘Ladoos’ were stored in pet boxes for three months to ascertain the changes in chemical, sensory and microbiological characteristics. An increasing trend was observed in TSS, reducing and total sugars but decreasing trend in titratable acidity, tannin and ash during three months of storage. The highest microbial count of 1.45×106 cfu/g was recorded in treatment T12 (desi + ginger + raw sugar) and the lowest of 0.41×106 cfu/g in T9 (NA-7 + cardamom + raw sugar) at the end of storage. On the basis of overall acceptability, T3 (NA-7 + cardamom + refined sugar) was found to be the best treatment. The storability study revealed that ‘Ladoos’ prepared from cultivar NA-7 have good-shelf life and can be kept for more than 90 days without affecting the quality attributes.